The Difficulties Of Managing Stress Assignment In The Pronunciation Iraqi Arabic Learners - Hussein AlMuselhy, Ahmed Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Few studies have focused on how Arabic-speaking students' L1 interference affects the stress they assign to English. This study investigates whether Arab learners' incorrect stress attribution is random or systematic. The research also intends to determine whether there is a connection between the phonotactic rules of stress placement in Arabic and the stress misplacement that Iraqi learners of English experience. At random, sixty students from three different English proficiency levels at Al Anbar University: lower-intermediate, upper-intermediate, and advanced. All of the morpho-syllabic word structures the students often mispronounced were included in the 50 stimulus words the teachers had them say. The recordings were analyzed by two independent raters and Praat spectrogram software. Research indicates that learners may have been influenced by other languages to do the following: a) consistently stress one syllable even though the word has different meanings depending on the other stress assignments; b) Misplace stress regardless of their level of English competence; c) Stress the penultimate syllable in the majority of polysyllabic words; d) Stress the second syllable in contracted negative auxiliary verbs; and e) Stress the second item in a compound noun rather than the first item in the composite noun.